Design and Analysis of an Engineering Structure for Fluid Dynamics Applications - Herb, Jackson (My University, 2020)
This study focuses on the design process and analysis of stress testing on a hydraulic valve. Using Autodesk Inventor, a valve was designed to regulate the flow of fluids such as gasses or liquids with the use of mechanical levers and springs. While designing this valve, constraints and regulations were provided, along with the purpose of the machine, in order to ensure that the valve can withstand the stresses it experiences during its continuous use. Constraints included size, material cost, and the valve must have had the ability to direct and block the flow of fluids. A stress analysis and parametric analysis is used on the valve. The stress analysis is to see where stress will be applied to the valve and how well the materials that were chosen preform. The parametric analysis shows how the valve reacts to different tasks and conditions, such as, different fluid types, temperatures, and pressures.